Diagnosis of calcific tendonitis of the rotator cuff by using susceptibility-weighted MR imaging - Noerenberg, Dominik; Ebersberger, Hans U.; Walter, Thula; Ockert, Ben; Knobloch, Gesine; Diederichs, Gerd; Hamm, Bernd; Makowski, Marcus R. (Radiology, 2016)
Purpose: To evaluate the diagnostic performance of susceptibilityweighted imaging (SWI) and standard shoulder joint magnetic resonance (MR) sequences in comparison to that of conventional radiography for the identification of calcifications in the rotator cuff in patients with calcific tendonitis. Materials and Methods: The institutional review board approved this prospective study. Written informed consent was obtained from all subjects. Fifty-four patients clinically suspected of having calcific tendonitis of the rotator cuff were included. On radiographs (the standard of reference), 27 patients had positive calcification findings, and 27 did not. Standard MR sequences and SWI, including magnitude and phase imaging, were performed. The diameter of calcifications was measured to assess intermodality correlations. Sensitivity, specificity, and intra- and interobserver agreement were calculated. Phantom measurements were performed to assess the detection limit of SWI. Results: Fifty-six calcifications were detected with radiography in 27 patients. Most (55 calcifications, 98%) could be identified as calcifications by using SWI. Standard T1- and T2-weighted sequences were used to identify 33 calcifications (59%). SWI yielded a sensitivity of 98% (95% confidence interval [CI]: 0.943, 1) and specificity of 96% (95% CI: 0.886, 1) for the identification of calcifications when compared with radiography. Standard rotator cuff MR sequences yielded a sensitivity of 59% (95% CI: 0.422, 0.758) and specificity of 67% (95% CI: 0.493, 0.847). Diameter measurements demonstrated a high correlation between SWI and radiography (R2 = 0.90), with overestimation of lesion diameter at SWI (mean 6 standard deviation for SWI, 7.6 mm 6 5.4; for radiography, 5.3 mm 6 5.1). SWI yielded higher interobserver agreement (R2 = 0.99, P <001; 95% CI: 0.989, 0.996) compared with standard MR sequences (R2 = 0.67, P = .62; 95% CI: 0.703, 0.899). In phantom experiments, SWI and computed tomography were used to identify small calcifications that were missed at radiography. Conclusion: SWI enables the reliable detection of calcifications in the rotator cuff in patients with calcific tendonitis by using conventional radiography as a reference and offers better sensitivity and specificity than standard rotator cuff MR sequences.
CRIS-Team Scopus Importer:2023-03-08